Research on Key Technical Standards of Railway Refrigerated Transport - 孙金平; 韩伯领; 刘广海 (Zhileng xuebao)
It is necessary to raise the current food preserving standards to meet the requirement of food quality and safety in railway refrigerated transport. In our research, the analysis on domestic and international food standards were performed. The current situation of the railway in our country and the market demand of perishable products were considered. The modification of technical standards of China railway refrigerated transport was conducted, including renewing the key quality indices and improving the transport rules.